The economics interests In Football - Raúl Fustes-Ross (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
The football is the most popular sport in the Word and the economics interests have been fundamentals in his increase and expansion; this idea is confirmed by the numerous competitions for even sexes with categories from National Championships to regional events, continentals, intercontinental, Olympic Games and World Cup from majors, the most important event where showed the most expensive and important merchandise: the players. All this sport mechanism is capitalized by the owners clubs, business trade associations and greats corporations in the host cities, the nations participating also those without participation but with many fans. Each and every one are customers, is a chance for increase the sales.